Polymeric Micellar Paclitaxel Plus Cisplatin Combined With Tislelizumab as the First‐Line Treatment of Advanced Unresectable Esophageal Squamous Cell Carcinoma: A Phase II Study - Xiaoyou Li; Jiamin Shi; Jinghua Zhu; Jingni Zhu; Fei Yan; Delin Liu; Guochun Cao (Thoracic Cancer)
ABSTRACT Background The current standard treatment for advanced and metastatic esophageal squamous cell carcinoma (ESCC) involves a combination of immunotherapy and chemotherapy, but paclitaxel's hormone preconditioning can reduce immune response and effectiveness. Polymeric micellar paclitaxel (Pm‐Pac), a nanoformulation, bypasses this issue, enhancing tumor permeability and retention. While Pm‐Pac has shown promise in non‐small cell lung cancer, its efficacy in ESCC is yet to be established. Methods This is a prospective phase II trial involving untreated stage IV ESCC receiving two cycles of Pm‐Pac, cisplatin, and tislelizumab. If no disease progression was observed, they received two additional cycles followed by a year of tislelizumab maintenance. Each 3‐week cycle consisted of Pm‐Pac (230 mg/m2), cisplatin (70 mg/m2), and tislelizumab (200 mg) on Day 1. The main objective was ORR. Secondary endpoints encompassed OS, PFS, DCR, and safety. Results Between September 1, 2022, and June 30, 2024, 23 patients were included in the study. The median follow‐up period was 14.8 months. The ORR stood at 69.6% (95% CI: 0.45–0.84) with a DCR of 100% (95% CI: 0.86–1.00). Out of the patients, 2 experienced complete responses, 14 had partial responses, and 7 maintained stable diseases. The mPFS was 10.8 months (95% CI: 0.26–0.632). The 1‐year OS rate was 69.6% (95% CI: 49.1–84.4). Notably, no grade 3 or higher treatment‐related adverse events or treatment‐linked fatalities were reported. Conclusions The combination of Pm‐Pac, cisplatin, and tislelizumab as an initial therapy for advanced ESCC is safe and effective and should be tested on a larger scale in the future. Trial Registration: Chinese Clinical Trial Registry: ChiCTR2400088576